Cybersecurity Challenges in Digital Innovation : A Strategic Management Perspective - Jakub Nowak; Katarzyna Lis; Magdalena Zielińska (Digital Innovation : International Journal of Management, 2024)
This article examines the growing cybersecurity challenges accompanying digital innovation and how strategic management can mitigate risks. Through case studies of cyberattacks on innovative technologies, the study outlines best practices for risk assessment, incident response, and integrating security into the innovation lifecycle. Findings emphasize the need for a proactive approach to cybersecurity in digital innovation strategies.